Prophetic Leadership for Sustainable Islamic Higher Education: A Systematic Literature Review of Transformative Values and SDG Alignment (2009–2024) - Khaeroni, Khaeroni; Ilzamudin, Ilzamudin; Subhan, Subhan (Gemilang Maju Publikasi Ilmiah (GMPI), 2025)
This study systematically synthesizes the prophetic values embedded in leadership models for Islamic higher education and analyzes their alignment with the United Nations’ Sustainable Development Goals (SDGs). Conducting a Systematic Literature Review (SLR) via the PRISMA protocol, the study reviews thirty-six peer-reviewed publications from Scopus, DOAJ, and Google Scholar spanning 2009–2024, focusing on leadership, ethics, innovation, sustainability, and Islamic higher education. The investigation identifies three central themes: the integration of ṣidq (truthfulness) and amānah (trustworthiness) in institutional governance and culture; the application of fatanāh (wisdom) and tablīgh (effective communication) in developing value-driven curricula, green campus initiatives, and ethical research management; and the use of adālah (justice) and shūrā (consultation) for participatory decision making. These findings suggest that prophetic leadership directly supports SDG 4 (Quality Education), SDG 9 (Industry, Innovation, and Infrastructure), SDG 10 (Reduced Inequalities), and SDG 16 (Peace, Justice, and Strong Institutions). The review concludes that prophetic leadership offers an innovative, ethically robust, and adaptive framework for reforming Islamic higher education towards sustainable development, expanding value-based leadership theory, and recommending practical directions for curriculum, leadership training, and governance, while highlighting pathways for further empirical study in organizational performance and SDG impact assessment.